Learning Environments and Proposals: Mayrit, a Different School - Alonso Alonso, Lara; Moreno González , Marta (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
In this article we will deal with learning and supportive environments in the second cycle of Early Childhood Education (3-6 years) taking as a reference the school Mayrit Escuela Activa. Firstly, we will focus on the learning environments and their dimensions. Subsequently, we will briefly revise the pedagogical approaches Reggio Emilia, Montessori and Waldorf, in which the learning environments are considered to be essential for the autonomous development of the individuals.  Furthermore, we will pay special attention to the teacher as a counsellor and facilitator, who should carefully observe, be pedagogically documented, design the learning environments and accompany the students. Finally, we will analyse the experience of Mayrit Escuela Activa, a school project that works using different learning environments, thus showing some of the educational proposals appeared during the course year. To sum up, we aim to show the reader the daily work of boys and girls and also of their monitors.
Keywords: learning environments; learning proposals; respectful monitoring; Early Childhood Education; Mayrit Escuela Activa